Sacred Resilience: The Intersection of Religious Beliefs and Psychological Well-being in Crisis Situation - Krishal Rangari; Ananya Gupta; Sneha Thakur; Sangeeta Kakkar (International Journal of Behavioral Sciences, 2025)
Background: The relationship between religious beliefs and psychological well-being has been a focal point of psychological research, particularly in the context of crises. Understanding how religious beliefs contribute to psychological resilience may enhance support mechanisms for individuals facing crises. Objective: This study aims to examine the intersection of religious beliefs and psychological resilience during crises, focusing on how faith-based practices influence coping strategies and overall mental health outcomes. Importance: This research underscores the significance of incorporating religious dimensions into psychological support frameworks, particularly in crisis contexts. Acknowledging the role of faith can improve mental health practices and enhance the well-being of individuals facing adversity. Methodology: A comprehensive review employed a qualitative methodology to synthesize existing literature on the relationship between religious beliefs and resilience. The research began with a systematic search of relevant academic databases, including PsycINFO, PubMed, and Google Scholar, using keywords such as religion, resilience, coping strategies, and psychological well-being. Results: The findings indicate that religious beliefs play a crucial role in enhancing psychological resilience in crises circumstances. Conclusions: Faith-based coping strategies not only mitigate distress but also foster a sense of community and support. Implications: Integrating spiritual care into mental health interventions may offer a more comprehensive approach to crisis management.
Keywords: Coping strategies; crisis intervention; psychological well-being; religious beliefs; sacred resilience